Controversy and doxa: sustainable food policy and the English vegetable sector?. Issue 9 (29th January 2021) - Moorhouse, Janice Veronica; Brennan, Ross
Abstract : Purpose: The authors explore the market agora and the shaping of markets as controversies over the meaning and practices related to sustainability evolved. This study aims to explore what happened in a market-oriented policy regime, which aimed to address sustainability in farming and food, to assess the impact of the policy on the vegetable sector in England and to consider whether the market-oriented policy regime created a more sustainable food system for Britain. Design/methodology/approach: The authors examined policy documents – agenda setting reports, policy frameworks and operational plans – and conducted interviews with experts – including policymakers, agronomists and the growers themselves, from across this heterogeneous production sector. Findings: The authors found that while controversy over the meaning of sustainability impacted on the evolution of food policy and grower business practices, market conceptualisations remained in a doxic mode – naturalised and beyond dispute throughout the market agora. Research limitations/implications: This is a study of a single sub-sector of the fruit and vegetable sector in a single European country and over a particular period of time. It presents a detailed, authentic representation of that sub-sector in context and diverse information sources were used to gain a variety of perspectives. However, it is acknowledged that this is a limited, qualitative study involving relatively few key informant interviews. Social implications: The authors' explanation suggests that market doxa limited how policymakers and market agora understood the economic challenges and the solutions that could be deployed for English vegetable growers, a sector so pivotal for sustainability. The authors propose that ideas from industrial marketing can be used to reignite controversy, challenge market doxa, and in doing so create space for progress in creating sustainable markets. Originality/value: The authors deploy an approach advocated by Blanchet and Depeyre (2016) and use controversy to explore the evolution of policy for sustainability and market shaping in the English vegetable sector agora. In doing so the authors create a novel explanation of why policy, which aimed to usher in a sustainable market, fell short of its aims and contribute to an under-researched area examining policy for sustainability in a B2B context.